The Influence of Top Management Support, System Usability, and Cybersecurity Readiness on the Digital HRM Effectiveness of Banking Sector Employees - Kushariyadi Kushariyadi; Iwan Henri Kusnadi; Enny Diah Astuti; Agus Setiono; Ayu Ratna Wulandari; Ahmad Nur Budi Utama (Yayasan Gema Bina Nusantara, 2026)
This study really wants to find out, in a kind of overarching way, how Top Management Support, System Usability, and Cybersecurity Readiness influence the Digital HRM Effectiveness for people working in the banking sector, yes, more or less. The research was conducted in a quantitative manner, through a survey approach aimed at banking workers. Purposive sampling was also used, but somehow it feels like it’s leaning a bit too much on one segment, like it’s overly directed toward that specific group. The data were gathered via an online survey, then processed using multiple linear regression. Before any hypothesis testing could even begin, validity and reliability checks were done, and of course the usual assumption scans were included, like normality, heteroscedasticity, and multicollinearity. So overall, it seems the dataset is a solid match. The findings indicate that Top Management Support, System Usability, and Cybersecurity Readiness all have a positive, and fairly strong impact on Digital HRM Effectiveness. That influence shows up in both partial effects and also, at the same time, through the combined model. Put more plainly, the results suggest that digital HRM in banking tends to be powered by manager backing, system clarity, and cybersecurity preparedness. In the end, this study contributes to the theoretical conversation on digital human resource management and also on how organizations undergo digital transition. It additionally provides hands-on direction for the banking industry, particularly for strengthening the real-world effectiveness of digital-based HRM.